1981
DOI: 10.2307/1924352
|View full text |Cite
|
Sign up to set email alerts
|

Labor Market Competition among Youths, White Women and Others

Abstract: This paper examines labor market effects of increased labor force participation Of youths and women. Using 1969 cross-section data for manufacturing, substitution elasticities for pairs of inputs from agerace-sex aggregates of labor and c?pital are estimated. Findings include strong substitution between youths and white females, and complementarity between many of the remaining inputs. Then, allowing either rigid or flexible youth wages, a ten percent increase in white female participation is simulated. Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 4 publications
2
41
1
2
Order By: Relevance
“…The third female age group is also a q-substitute for the first female group, although complementary with the second, and the second female age group is a q-substitute for the first male group, with an elasticity of complementarity equal to that between F3 and Ml. These results support the Grant and Hamermesh (1981) finding of a high degree of substitutability between adult (white) women and young labour, and the elasticity of complementarity they find between these groups is of the same order of magnitude as the elasticity we find between F3 and Ml.3…”
Section: Change In Quantity Ofsupporting
confidence: 90%
See 2 more Smart Citations
“…The third female age group is also a q-substitute for the first female group, although complementary with the second, and the second female age group is a q-substitute for the first male group, with an elasticity of complementarity equal to that between F3 and Ml. These results support the Grant and Hamermesh (1981) finding of a high degree of substitutability between adult (white) women and young labour, and the elasticity of complementarity they find between these groups is of the same order of magnitude as the elasticity we find between F3 and Ml.3…”
Section: Change In Quantity Ofsupporting
confidence: 90%
“…The differences between Merrilees' results and those surveyed by Hamermesh and Grant (1979) do not appear to be due to the broad groupings Merrilees uses, since Grant and Hamermesh (1981) use similarly broad groupings and find a significant degree of substitutability. It may be due to the approach Merrilees takes to estimating the degree of substitutability, which will be referred to in the following section.…”
Section: I T E R a T U R E Reviewmentioning
confidence: 72%
See 1 more Smart Citation
“…The role of children in income generation is well documented and the child labor literature has identified linkages between adult and child labor. For example, in some economies, children and women are found to be substitute sources of labor, while children and men are found to be complements in production (Grant & Hamermesh, 1981). But such investigations have not explored whether and how the productive role of children may vary among household headship types.…”
Section: Introductionmentioning
confidence: 99%
“…A number of empirical studies have confirmed that white and nonwhite labour are imperfect substitutes: Grant and Hamermesh (1981) find that black adults are imperfect substitutes for white men and complements to white women and youths; Borjas (1983) provides evidence indicating that black males are imperfect substitutes for white males, but that Hispanics and white males are complementary; Borjas (1987) shows that black natives are imperfect substitutes for white natives, whilst Kahanec (2006) finds that non-whites are complementary to whites.…”
Section: Introductionmentioning
confidence: 99%